2020
DOI: 10.1590/2317-1782/20202019071
|View full text |Cite
|
Sign up to set email alerts
|

Senso de Coerência e o medo de falar em público em universitários

Abstract: RESUMO Objetivo: Testar a associação entre o Senso de Coerência (SOC) e o medo de falar em público em universitários. Método: Estudo transversal, com amostra de 1.124 estudantes de cursos de graduação de uma universidade pública brasileira. Foi utilizado questionário online dividido em três blocos: o primeiro avaliou os dados sociodemográficos e os sintomas somáticos do medo de falar em público; o segundo avaliou o SOC, por meio do questionário SOC-13; e o terceiro foi composto pela Escala para Autoavaliação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The positive association between the sense of coherence and quality of life can contribute to better academic performance and professional profile, and a greater sense of coherence was associated with less somatic stress symptom manifestation., as shown by Sójka A et al in their study with 324 medical student [ 48 ]. Pantuza et al [ 14 ], demonstrated that college students with higher SOC had more confidence to speak in public and experienced less labored breathing. Thus, being able to recognize stressful situations, mobilize resources to promote effective coping, and find solutions to resolve situations and difficulties, in order to have a better quality of lifestyle and health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive association between the sense of coherence and quality of life can contribute to better academic performance and professional profile, and a greater sense of coherence was associated with less somatic stress symptom manifestation., as shown by Sójka A et al in their study with 324 medical student [ 48 ]. Pantuza et al [ 14 ], demonstrated that college students with higher SOC had more confidence to speak in public and experienced less labored breathing. Thus, being able to recognize stressful situations, mobilize resources to promote effective coping, and find solutions to resolve situations and difficulties, in order to have a better quality of lifestyle and health.…”
Section: Discussionmentioning
confidence: 99%
“…The central concept in Antonovsky's Salutogenesis Theory, which helps people deal with difficult and stressful circumstances better, is the Sense of Coherence (SOC) [11,12]. Cognitive (understanding), behavioral (management), and motivational (meaning) are its three primary elements [13,14]. This idea contends that a strong sense of coherence enhances motivation and purpose in one's perception of the world, leading to lower levels of stress and anxiety [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao explorar o SOC em PPL e encontrou-se índices de SOC forte em 33,13 %, em detrimento de SOC moderado em 65,95% e fraco em 0,92%. O nível de SOC moderado, apesar de serem populações diferentes, foi encontrada também em 45 jovens apreendidos em centro de menores na Espanha e em 70 PPL Polonesas, e, diferindo de estudo realizado com 1124estudantes universitários brasileiros que apresentou maior prevalência de SOC alto (o primeiro e terceiro usando versão SOC-13 e o segundo SOC-29) [18][19][20] . Estudo espanhol utilizando a escala SOC-13 também apresentou predomínio de SOC moderado em 124 PPL 21 .…”
Section: Discussionunclassified
“…These resources can neutralize several stressors, that is, can facilitate the management of tensions and help in coping with daily activities so as to promote health. [1][2][3] The Salutogenic Theory has a central element called Sense of Coherence (SOC), which measures the ability to cope of individuals in everyday situations. This element is related to mental well-being and can be understood based on the ability to experience stressful situations, understanding events, their meanings, and managing tensions.…”
Section: Introductionmentioning
confidence: 99%